The Work-Life Balance of Public Sector Employees in Poland in the Context of Available Legal Regulations - Szczudlińska-Kanoś, Agnieszka (Journal of Public Governance, 2024)
Objective: The purpose of this article is to present changes in the legal system in Poland regarding work-life balance and to confront them with the expectations of public sector employees in this area.Research Design & Methods: The study is based on the analysis of literature, normative acts, and the results of nationwide surveys conducted in 2021 in Poland based on sample of 3,114 public sector employees.Findings: Research shows that remote work, the ability to choose working hours, and informal working time arrangements are solutions that would significantly help public sector employees reconcile work and private life.Implications/Recommendations: The analysis of legal acts shows changes in the approach to the WLB concept over the last decade in Poland and the development of solutions facilitating the reconciliation of professional and personal life. These changes are expected by employees. Difficulties related to the implementation of WLB tools in public organisations are identified resulting from their specific structure, procedures, and budget constraints.Contribution/Value Added: The article is a source of knowledge for theoreticians, practitioners, employers, and public authorities. The presented results can be used when making decisions aimed at optimising the working conditions of public sector employees and adapting them to changing social needs and legal requirements.Article classification: research article